2013
DOI: 10.1038/ncb2767
|View full text |Cite
|
Sign up to set email alerts
|

The perivascular niche regulates breast tumour dormancy

Abstract: In a significant fraction of breast cancer patients, distant metastases emerge after years or even decades of latency. How disseminated tumor cells (DTCs) are kept dormant, and what ‘wakes them up’, are fundamental problems in tumor biology. To address these questions, we utilized metastasis assays in mice to show that dormant DTCs reside upon microvasculature of lung, bone marrow and brain. We then engineered organotypic microvascular niches to determine whether endothelial cells directly influence breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
1,054
3
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 979 publications
(1,100 citation statements)
references
References 61 publications
33
1,054
3
10
Order By: Relevance
“…SOCS3 is a tumor suppressor, and its function is lost in liver, lung, and squamous head and neck cancer 98. Molecular receptor systems, such as transforming growth factor β (TGFβ) receptors, induce a growth state and axonal sprouting in stroke13 and also are key molecules in metastatic transformation in cancer, such as the epithelial–mesenchymal transition 97, 99, 100. Recently described microRNAs that induce neural repair or axonal growth responses, such as miR‐9 and miR‐133,101, 102 are also closely linked to oncogenesis 103, 104, 105.…”
Section: Engaging Cns Tissue Regeneration Is Like Activating a Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…SOCS3 is a tumor suppressor, and its function is lost in liver, lung, and squamous head and neck cancer 98. Molecular receptor systems, such as transforming growth factor β (TGFβ) receptors, induce a growth state and axonal sprouting in stroke13 and also are key molecules in metastatic transformation in cancer, such as the epithelial–mesenchymal transition 97, 99, 100. Recently described microRNAs that induce neural repair or axonal growth responses, such as miR‐9 and miR‐133,101, 102 are also closely linked to oncogenesis 103, 104, 105.…”
Section: Engaging Cns Tissue Regeneration Is Like Activating a Cancermentioning
confidence: 99%
“…Following a stroke, progenitor cells are induced into a growth program that involves cell division, migration to a tropic cue, and association with angiogenic vessels 6, 7, 8. This is a cellular response similar to tumor metastasis, in which primary tumor cells invade adjacent tissue, circulate, and localize to angiogenic vessels 97, 99. Like metastatic tumor cells,100 migrating progenitors after stroke secrete matrix metalloproteinases to digest their way to the target tissue 106.…”
Section: Engaging Cns Tissue Regeneration Is Like Activating a Cancermentioning
confidence: 99%
“…Recent work has linked the ECM in tumors to dormancy [9], resistance to chemotherapy or radiation [10][11][12], metastasis and metastasis tropism [13] again demonstrating the importance of understanding cell-ECM interactions. It has become apparent from both in vitro and clinical work that the ECM signals to cells through both biochemical and physical means with complex interactions between ECM composition, splicing, microstructure, and biomechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Bissell and colleagues demonstrated that POSTN surrounding the tip cells of the neovasculature awakens the dormant disseminated breast tumor cells and augments metastatic tumor outgrowth. 11 Recently, we further showed that POSTN is a novel component of immunosuppressive premetastatic niches and is exploited by breast tumor cells to facilitate lung metastasis. 12 These studies suggest that POSTN plays critical roles in various tumor microenvironments, including the cancer stem cell niche, 6,10 the perivascular niche 11 and the premetastatic niche 12 during tumor metastasis, and may represent a novel diagnostic and therapeutic target for tumor metastasis.…”
mentioning
confidence: 99%
“…11 Recently, we further showed that POSTN is a novel component of immunosuppressive premetastatic niches and is exploited by breast tumor cells to facilitate lung metastasis. 12 These studies suggest that POSTN plays critical roles in various tumor microenvironments, including the cancer stem cell niche, 6,10 the perivascular niche 11 and the premetastatic niche 12 during tumor metastasis, and may represent a novel diagnostic and therapeutic target for tumor metastasis. While the expression pattern and function of POSTN in the development and metastasis of solid tumors have been extensively investigated, not much is known about its roles in hematological malignancies.…”
mentioning
confidence: 99%